2018
DOI: 10.1021/acsami.8b15212
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Room Temperature-Grown Inorganic Perovskite Quantum Dots for Highly Efficient Inverted Light-Emitting Diodes

Abstract: Inorganic cesium lead bromide quantum dots (CsPbBr 3 QDs) are usually synthesized via a high-temperature process (hot injection, HI). This process is similar to that used for the synthesis of other semiconductor QDs (i.e., CdSe@ZnS), which limits their potential cost advantage. CsPbBr 3 QDs can also be synthesized at room temperature (RT) in a low cost and easily scalable process, which, thus, is one of the greatest advantages of the CsPbBr 3 QDs. However, light-emitting diodes (LEDs) fabricated using RT-QDs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 47 publications
(87 reference statements)
0
46
1
Order By: Relevance
“…The same group expanded their approach soon after, introducing a ligand exchange protocol with didodecyldimethylammonium bromide (DDAB). [67] They demonstrated that DDAB ligands were more resistant to antisolvent washing and annealing, such that oleic acid and oleylamine are mostly removed, while DDAB mostly remained. This hypothesis is illustrated in Figure 4.…”
Section: Inorganic Perovskite Nanocrystalsmentioning
confidence: 99%
See 3 more Smart Citations
“…The same group expanded their approach soon after, introducing a ligand exchange protocol with didodecyldimethylammonium bromide (DDAB). [67] They demonstrated that DDAB ligands were more resistant to antisolvent washing and annealing, such that oleic acid and oleylamine are mostly removed, while DDAB mostly remained. This hypothesis is illustrated in Figure 4.…”
Section: Inorganic Perovskite Nanocrystalsmentioning
confidence: 99%
“…Reproduced with permission. [67] Copyright 2018, American Chemical Society. www.advancedsciencenews.com…”
Section: Polar Solvent-free Synthesesmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 These properties make them ideal candidates for the next generation of low cost solar cells, PeLEDs, laser, and photosensor. [3][4][5]14,15 Organic perovskites are widely used in laboratories to fabricate high performance devices, however their crystal structure easily degrades at moderate temperature or low relative humidity. Thus, allinorganic PeLEDs are expected to exhibit a higher stability under both storage and operating conditions.…”
Section: Introductionmentioning
confidence: 99%